Juvenile Delinquency Criminogenic Factor - Indah Rufiatun (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
Children often commit unlawful acts. The causative factors of juvenile delinquency need to be known to prevent the occurrence of juvenile delinquency in the future. The purpose of this study was to explain the criminal forms of juvenile delinquency and explain the criminogenic factor juvenile delinquency. The type of research used is criminology research. Data sources are obtained from interviews, questionnaire deployments, and literature studies. The results showed that juvenile delinquency in Jepara Regency, in 2019 and 2020, in terms of crime decreased, but in terms of the severity of crimes committed by children increased. Encouragement from within the child and the surrounding environment that is less harmonious causes the child to do juvenile delinquency.